Anticipation of Student Ideas In Designing Sierpinsky Square Batik Using Maple - Erfan Yudianto (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2021)
This research is motivated by the importance that students have the ability to anticipate. The anticipation skill is needed by students to complete fractal batik designs (Sierpinsky) by using maple so that the resulting ideas matches the original expected ideas. The purpose of this research is to enable students to use maple to design Sierpinsky square batik. Data in this research were collected by tests, interviews and observations. The results showed that students frequently used analytical and exponential anticipation skills. Keywords: Analytic Anticipation, Exploratory Anticipation, Sierpinsky, Sierpinsky Batik.